MoS2-Fe3C composite: a dual-functional material for methylene blue adsorption and photocatalysis in sustainable energy systems - Amal T. Mogharbel; Amnah S. Al Zbedy; Mona H. Alhalafi; Ahmed H. Jawhari; Zehbah A. Al-Ahmed; Omaymah Alaysuy; Sahar Sallam; Nashwa M. El-Metwaly (Journal of Saudi Chemical Society)
Abstract The removal of industrial pollutants from water is a critical global challenge, necessitating the development of efficient materials for water treatment. In this study, a novel composite was synthesized, consisting of molybdenum disulfide (MoS₂) prepared via hydrothermal synthesis and iron carbide (Fe₃C) obtained by carburizing iron oxalate at 500 °C. The individual materials and the composite were characterized using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and BET surface area analysis, confirming the successful formation of the composite with the desired structure. The adsorption and photocatalytic performance of the synthesized materials were evaluated for methylene blue (MB) removal from water. The results demonstrated a significant improvement in removal efficiency when using the composite compared with pure MoS2. The removal efficiency increased from 38.9 and 64.7% for MoS₂ to 44.5% and 98.3% for the composite in dark and illuminated conditions, respectively. This enhancement is attributed to the synergistic interaction between adsorption and photocatalytic degradation, leading to higher adsorption capacity from 11.71 mg.g−1 to 42.95 mg.g −1 and self-regeneration of active sites. These findings highlight the composite as a promising candidate for industrial dye removal and efficient water purification in the presence of sustainable light energy.